Políticas públicas habitacionais e segregação socioespacial: o bairro Jardins Mangueiral na região administrativa de São Sebastião (DF) - (:unkn) unknown (Universidade Federal de Goiás, 2015)
The city´s increase demands a transformations of urban space and the unplanned occupation produces many problems to population, Therefore, the urban planning and its implantation is essential to organize and, consequently, offer better condition of living. The Urban Geography seek to understand, analyze and explain the differences and similarity between the cities, as well as localization and modern pattern establishment on academician discussion. Different spatial settlement is forming on housing section, specifically in Brasilia, Distrito Federal. The dwelling represents something widely discussed in this context. The architectural structure of the houses, your localization toward the downtown, the housing market, and effective housing scheme since 2003 means the way to organize and transform the urban space. Brasilia, as a planned city, symbolizes on the economical and spatial context an island that separates the population of Distrito Federal (DF) on different Administrative Zones (Regiões Administrativas) according with socioeconomic criterions. The institutionalized planning benefits in many ways people, according with theirs social class. So the current housing political perpetuate the way of the city´s organization, offering the best home´s frame and the best services and urban equipment on the Administrative Zones next to the downtown, where is organized by the spending power of the people who lives there. On the federal program “Minha Casa, Minha Vida” were installed the first private and public association on housing development, resulting on the planning borough Jardins Mangueiral, located at São Sebastião (DF). This borough was related on related on experience survey, considering the area expected on Plano Diretor de Ordenamento Territorial do Distrito Federal, 2009. The methodological procedure adopted on this activity accomplishment the theoretical research, the documental research and the study field surveys with data acquisition about demographic and socioeconomic features of population living on the borough and the law established on the housing program. The main objective is to understand the relationship between urban planning, housing policies and private and public association in the construction of planning borough for different socioeconomic classes in the Distrito Federal. The study field survey was made on 2014. The data collection instrument was: participant observation, photographic records and a questionnaire applied to a hundred residents of Jardins Mangueiral. The procedures adopted for collecting, analyzing, organizing and interpretation of data beheld the proposed objectives, to discuss: a) the socio-spatial segregation in Distrito Federal; the relationship between the planned boroughs as a means of production and the occupation and transformation of urban space; b) to describe the socioeconomic changes that are occurring in São Sebastião (DF), with the construction of the new Borough and c) to point out the positive and negative aspects that characterize the Jardins Mangueiral, showing the desires of the local population, which, in spite of living in a planned residential borough, needs basic services and urban facilities in daily life. In the field of the Geography, the relevance of the research involves the analysis to understand the processes related to production of urban space linking the public housing policies, the urban planning and the new private and public associations in the housing sector, and associate these policies with the socio-spatial segregation brought in the Distrito Federal.
Public policy and housing segregation socio: the neighborthood Mangueiral Gardens administrative region of São Sebastião (DF)
Keywords: Políticas habitacionais; Planejamento urbano; Parceria público-privada; Moradia; Bairro Jardins Mangueiral, São Sebastião (DF); Housing political; Urban planning; Private and public association; Dwelling; Borough Jardins Mangueiral, São Sebastião (DF); CIENCIAS HUMANAS::GEOGRAFIA